2018
DOI: 10.1016/j.ehj.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise training on heart rate recovery in patients post anterior myocardial infarction

Abstract: BackgroundRegular exercise training has been shown to reduce mortality, improve functional capacity; and control the risk factors in myocardial infarction (MI) patients. Heart rate recovery (HRR) is a strong independent mortality predictor in patients with previous MI.AimThe main objective of this study was to investigate the impact of exercise training on heart rate recovery in patients post anterior myocardial infarction.MethodsWe recruited patients one month after having anterior MI who were referred to car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 11 publications
5
19
1
1
Order By: Relevance
“…Similar results were seen in other studies comparing the effect of 12-week cardiac rehabilitation programs on heart rate recovery in 1 min for ischemic heart disease patients recovering from acute myocardial infraction all showing a significant increase in heart rate recovery with cardiac rehabilitation [ 24 , 29 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results were seen in other studies comparing the effect of 12-week cardiac rehabilitation programs on heart rate recovery in 1 min for ischemic heart disease patients recovering from acute myocardial infraction all showing a significant increase in heart rate recovery with cardiac rehabilitation [ 24 , 29 ].…”
Section: Discussionsupporting
confidence: 88%
“…Enrollment in a cardiac rehabilitation program is recommended for all patients with stable coronary artery disease following MI and PCI [ 20 22 ]. Benefits of participating in the cardiac rehabilitation program provided at our institution were previously reported and are comparable to well-established programs elsewhere [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 75%
“…The full-text versions of the remaining articles were reviewed for eligibility resulting in the exclusion of 224 for the reasons noted. Ultimately, 62 studies were included from the search, reporting on 60 unique patient samples 23 25–86…”
Section: Resultsmentioning
confidence: 99%
“…Exercise training concerns planned and organized body movement to improve physical capacities; examples include swimming, yoga, aerobic and resistance/strength exercise, and so on (Tulpule and Tulpule, 1980;Ferrera et al, 2014;Moraes-Silva et al, 2017;Ostman et al, 2017). After MI, Exercise training may induce positive effects; improve QoL, metabolic equivalents (METs), circulation function, and heart rate; and lower the risk of chronic disease and all-cause mortality (Greif et al, 1995;Adams et al, 2017;Elshazly et al, 2018;Mora and Valencia, 2018) (as shown in Figure 1).…”
Section: The Benefits Of Exercise For MImentioning
confidence: 99%